(untitled) (Belügyi Szemle, 2025)
Aim: The aim of the research is to use the Healthy Organization Model to explore what strengths and areas for development there are in the public administration, what factors, processes, and characteristics there are in the public administration in which the public administration works very well and effectively based on the interview results of some organizations of the central public administration. In this paper, I will focus on one of the 20 health-disease dimensions of the Healthy Organization Model, which is decision-making. I will illustrate its functioning through the examples of a few organizations in the central public administration. Methodology: Conducting semi-structured interviews with leaders at various levels in several central public administration organizations using an interview guide based on the Healthy Organization Model. Findings: There are organizations and units where this area functions exemplary; there are organizations and units where they face more difficulties in the area of decision-making, but positive changes and efforts to solve difficulties are visible. The leaders use several methods to make decision-making effective within their jurisdiction, and they suggest possible solutions to the difficulties in decision-making process. Value: Based on the leader interviews, it was revealed which mechanism of decision making in the central public administration is functioning exemplary, and which mechanisms are functioning not so efficient. In those organizations where certain mechanisms need to be developed, there may be possible to develop them with the good practices applied in other organizations.